Suicide Prevention at Workplace: Assessing Information Technology (IT) Professionals’ Willingness to Intervene with Colleagues - Muhammed Noorudheen; Anish V. Cherian; P. V. Prathyusha; K. S. Meena; R. Dhanasekara Pandian; Binukumar Bhaskarapillai (Journal of Psychiatry Spectrum)
Background: Suicide is a leading public health concern in India. Information technology (IT) professionals face various stressors, and studies show that job stressors could be risk factors for suicidal behaviors. Given that individuals spend a substantial amount of time at work, institutionalized prevention programs need to be leveraged in workplaces. Objectives: This study aims to assess the willingness of IT professionals to intervene in suicide prevention, their engagement in gatekeeper behaviors, and their attitudes toward suicide-related stigma. Materials and Methods: An online survey was conducted among IT professionals in Bengaluru city using purposive and snowball sampling methods. Tools used included a sociodemographic profile, willingness to intervene against suicide questionnaire, gatekeeper behavior scale, and stigma of suicide scale (short form). Pearson’s correlation coefficient was used to analyze the relationship between variables. Results: A total of 40 respondents participated in the study. The findings indicate that the willingness to intervene among IT professionals with a suicidal colleague is at an average level. In addition, the likelihood and self-efficacy components of gatekeeper behavior were positively correlated with the willingness to intervene. Conclusion: Willingness to intervene is a primary step in predicting suicide prevention behaviors. While the study indicates an average level of willingness to intervene, the small sample size limits the generalizability of the findings and may impact the result validity. Nonetheless, implementing suicide prevention training and incorporating peer-based interventions into industrial well-being programs could play a vital role in identifying and reducing suicidal risks in workplaces.